LEGAL PROTECTION FOR CHILDREN AS VICTIMS OF SEXUAL VIOLENCE BASED ON THE PERPECTIVE OF LAW NUMBER 12 OF 2022 CONCERNING SEXUAL VIOLENCE CRIMINAL ACTION - Rizky Ayu; T Riza Zarzani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The number of cases of violence against children is quite increasing. Based on the results of data from the Symphony or the Ministry of Women's Empowerment and Child Protection, there have been 1,848, related to cases of sexual violence that have a tremendous impact, such as increased risks regarding economic problems, education, aspects of community life in terms of health, politics, violence against children and their families, high levels of stress and even cases of violence, so that a significant impact occurs on the lives of children and their families. So efforts are needed that must be carried out in a coordinated manner in an effort to provide protection from sexual abuse of children in the present. This study discusses legal arrangements, forms of protection and solutions in preventing the reduction in the number of children as victims of sexual violence. The research specifications used in this study are in the form of descriptive analysis with a normative legal research approach. Data collection techniques carried out using literature studies related to children's problems as victims of sexual violence. Factors that underlie children vulnerable to becoming victims of sexual violence are lack of supervision from parents, lack of community concern, and a deterrent effect for perpetrators. The protection provided to vulnerable children as victims of sexual violence has been regulated in Law Number. 31 of 2014 On the protection of Witnesses and Koeban contained in article 5 that victims have their rights as victims. As well as efforts that can be made to prevent children from becoming victims of sexual violence, an institution is needed to understand the policies for child safety.